Supporting Context Events in an Interactive TV Platform - Mielke, Izon Thomaz; Costa, Patrícia Dockhorn; Vale, Igor Magri (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2011: Anais do III Simpósio Brasileiro de Computação Ubíqua e Pervasiva, 2011)
This paper aims at investigating functionality of the middleware Ginga that can be leveraged to build context-aware interactive TV applications. We identify the elements of the middleware that can effectively be used to realize each of the particular aspects of context-awareness, namely capturing, processing and reacting upon context changes. We present a prototype application in order to illustrate how these elements have been identified and how they can be used. We also define a programming framework that facilitates capturing and distributing context events in this interactive TV platform.